The leadership patterns of the headmasters in public schools in The Directorate of Marka in Amman- Jordan and their relation to job satisfaction from the teacher’s point of view - Sa’adeh, Samira Abdel Rahman (Journal of Educational and Psychological Sciences, 2019)
This study aims to stand on the relation between the leadership patterns that are followed by headmasters in public schools and the degree of job satisfaction of teachers in The Directorate of Marka in Amman- Jordan. The researcher used the descriptive approach، the tool was represented in applying Abbas scale 2015.The study members are the teachers in public schools in The Directorate of Marka / Amman that are (100) teachers developed. The result is that there is a positive relation between the dimensional leadership patterns and job satisfaction of teachers، it also showed that job satisfaction reach t(0، 76 ) and the level of leadership is average for all which is (3، 46) .The transfer pattern has the highest average arithmetic among the four patterns which is (3، 58) then the procedural pattern (3، 46)، after thar non- interference pattern (3، 39)، finally the democratic pattern (3، 28)، all with a verbal estimate . The results also showed that job satisfaction of teachers in public schools of the leadership patterns are average grade. It recorded (3.32) with average grade too. According to the results several recommendations and proposals were made to improve leadership pattern and to increase job satisfaction degree.